The stellar Mg/Si, C/O, Ca/Si, Al/Si, Na/Si, and Fe/Si ratios and the mineral diversity of rocky exoplanets - Futó Péter; Gucsik Arnold (Open Astronomy)
The bulk planetary compositions are thought to be consistent with the chemical abundances of their host stars. The abundances of eight key rock-forming elements and the key planetary abundance ratios in G- and F-type main sequence stars located in the solar neighborhood within 50 pc were statistically analyzed. The averaged C/O, Mg/Si, and Fe/Si elemental ratios of the planetary systems play a crucial role in the chemical composition and mineralogy of a rocky planet's interior. We also investigated the variation of the calculated Ca/Si, Al/Si, Na/Si, and Fe/Si ratios in the samples of the examined stars utilizing the Ca, Al, Na, and Fe abundances from the catalog and then attempted to establish plausible occurrence trends of the analyzed abundance ratios for the rocky planet population at near-solar galactocentric distances. Considering these results, we provide simple predictions for the most likely bulk compositions of the potential rocky planets. We apply our results to compare them to the solar averaged abundance ratios, showing that the key elemental ratios for terrestrial planet composition in the Solar System are not typical among most of the studied stellar samples.